Sustainable additive manufacturing: challenges and opportunities of recycling plastic waste for 3D printing filaments - Sharma A.; Kumar M.; Sharma A. (My University, 2025)
The escalating global crisis of plastic waste necessitates innovative and sustainable approaches to its management. This study explores a novel method; the transformation of discarded plastic materials into high quality 3D printing filaments, offering a promising solution to this pervasive environmental challenge. This review paper delves into the prospects of leveraging plastic waste recycling for the production of 3D printing filaments, thereby advancing the cause of sustainable additive manufacturing. The investigation encompasses a comprehensive examination of the recycling process, encompassing waste collection, sorting, and filament extrusion. The outcomes of this study underscore the substantial potential of recycling plastic waste for 3D printing filaments as a sustainable alternative to conventional manufacturing. This review also delves into the polymer degradation phenomenon, assessment of properties of recycled polymers, and environmental impact assessment, conducting a comparative analysis with traditional filament production methods. This paper advances the application of recycling plastic waste for 3D printing filaments, offering a tangible and immediate response to the global plastic waste crisis. © Indian Academy of Sciences 2025.